One Week in Kabul: An Unpublished Travelogue of Ale Ahmad Suroor - Rafi ud Din Hashmi (بازیافت)
Prof. Aal-e-Ahmed Suroor was a prominent writer, critic and Iqbaliat expert. He was the editor of Anjuman Taraqi-e-Urdu's weekly news letter "Hamari Zabaan" published from Ali Garh. He had to travel to Kabul in June 1994 for one week. He was nominated as an observer in an international translation seminar. While coming back to India he compiled a travelogue whose title was "Kabul Mein Aik Hafta". This is an unedited article which has not been indicated in any book or index. So, here, it is being revealed with some necessary notes.